The Existence Of Cyber Literature: Literary Window As Online Literary Publication Media For Writers - Wa Mirna; Rahma Anugraheny (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The existence of Jendela Sastra provides a great opportunity for writers and readers to be more connected and collaborate in creating literary works, creating a more active community, and exploring new monetization potential that is more sustainable. The purpose of this research is to describe the existence of the Jendela Sastra platform as an online literary publication media for writers. The method used in this research is descriptive analysis method. The results of this study consist of four parts, namely: (1) the role of Jendela Sastra in the dissemination of literary works, including (a) wider accessibility, (b) diversity of literary genres and styles, (c) use of technology in the delivery of literature, (2) interaction between writers and readers, including (a) creative dialog, and (b) active participation of readers, (3) challenges in digital literary media, including (a) quality issues and content curators, (b) copyright infringement, and (c) monetization and sustainability, and (3) opportunities for the development of digital literary media, including (a) increased access to literature to the international community, and (b) collaboration between writers and readers.